A novel coumarin-based ratiometric near-infrared fluorescence probe for hypochlorous acid in living cells. (October 2020) - Nie, Jing; Sun, Hao; Miao, Baoxi; Ni, Zhonghai
Abstract: A new near-infrared fluorescence compound ( E )-2-(3-(2-(7-(diethylamino)-2-oxo-2 H -chromen-3-yl)vinyl)-5, 5-dimethylcyclohex-2-en-1-ylidene)malononitrile (DL) constructed by a coumarin moiety and a malononitrile derivative has been designed and synthesized. Compound DL shows strong NIR emission located at 713 nm and good signal resolution. The ratiometric emission (496/713 nm) can ensure accurate detection of hypochlorous acid (HOCl) in vivo and in vitro, respectively. In addition, compound DL possesses high selectivity and sensitivity for specific determination of HOCl. Moreover, fluorescence imaging shows that compound DL can be used as a probe for ratiometric visualization of exogenous and endogenous HOCl in HeLa cells. Highlights: Probe DL is a ratiometric response (NIR) fluorescence probe. Probe DL shows s significant ratiometric fluorescence switching for HOCl/OCl − detection with high sensitivity, selectivity. Probe DL displays excellent performance for detecting exogenous and endogenous HOCl/OCl − in living HeLa cells.